2003
DOI: 10.1007/bf03006667
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of direct radionuclide cystography and voiding direct cystography in the detection of vesicoureteral reflux

Abstract: Although the results of these two methods did not show a significant difference, DRNC offers a high sensitivity in the younger age group whereas VCUG seems to be more sensitive in the older age group. DRNC also offers continuous recording during the study, ease of assessment and lower radiation dose to the gonads, which makes it a preferable method for the initial diagnosis and follow-up of VUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…There were no false-negatives detected by iMRVC, giving a high sensitivity, but 3 renal units were considered positive on iMRVC where they were negative on MCUG, giving a 78% specificity. There are several possible reasons for this discrepancy, whether technical or physiological: VUR may be a transient phenomenon, as techniques such as DRC have different sensitivity to MCUG [24], and repeated bladder filling/voiding cycles increases VUR detection: a second cycle can increase VUR detection by between 12% (CEUS [29]) and 20% (during MCUG [7,9]). The sensitivity of a single-cycle MCUG may be low, but many centres (including ours) perform only one cycle due to concerns about dose, at the expense of potential false-negative results [6], despite three cycles advised in recent European recommendations [30].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There were no false-negatives detected by iMRVC, giving a high sensitivity, but 3 renal units were considered positive on iMRVC where they were negative on MCUG, giving a 78% specificity. There are several possible reasons for this discrepancy, whether technical or physiological: VUR may be a transient phenomenon, as techniques such as DRC have different sensitivity to MCUG [24], and repeated bladder filling/voiding cycles increases VUR detection: a second cycle can increase VUR detection by between 12% (CEUS [29]) and 20% (during MCUG [7,9]). The sensitivity of a single-cycle MCUG may be low, but many centres (including ours) perform only one cycle due to concerns about dose, at the expense of potential false-negative results [6], despite three cycles advised in recent European recommendations [30].…”
Section: Discussionmentioning
confidence: 96%
“…Direct Radionuclide Cystography (DRC) gives a 10-fold lower radiation burden to the gonads than MCUG, allows continuous recording during the study and may be more sensitive in a younger age group than MCUG [24]. However, like CEUS and iMRVC, DRC requires bladder catheterisation and therefore a trauma and infection risk.…”
Section: Discussionmentioning
confidence: 98%
“…In the diagnosis of VUR the most important modality is voiding cystoureterogram however,, this is an invasive method with high radiation dose. Direct radionuclide cystography is a sensitive method and has lower radiation dose compared to voiding [7] however,, do not provide anatomical detail thus not preferred as first imaging method in the male patients at the first diagnosis. In a recent comparative study the direct radionuclide methods has been found to be more correlated with DMSA findings and clinical results [8].…”
Section: Discussionmentioning
confidence: 99%
“…It neither tries to endorse nor contradict the already established features and roles of VCUG or conventional DRC. [911]…”
Section: Discussionmentioning
confidence: 99%